Pengembangan Flipbook Interaktif Berbantuan Canva Terhadap Kemampuan Pemecahan Masalah Pada Materi Statistika Kelas VIII - Resa, Maria Reza Fenon; Astuti, Reni; Firdaus, Muhamad (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study was motivated by students’ low mathematical problem-solving skills and the suboptimal use of engaging and interactive learning media in mathematics instruction. The purpose of this study was to determine the validity, practicality, and effectiveness of an interactive flipbook created using Canva on problem-solving skills in statistics for eighth-grade students at SMP Negeri 21 in Pontianak. This study employed the Research and Development (R&D) method using a modified 3D version of the 4D development model, namely define, design, and develop. The research subjects consisted of several validators, including subject matter experts and media experts, as well as 28 eighth-grade students from Class VIII C at SMP Negeri 21 in Pontianak. Data collection techniques included validation sheets, teacher and student response questionnaires, and problem-solving ability tests. The results showed that the validity level of the Canva-assisted interactive flipbook achieved an average percentage of 88.58%, meeting the criteria for “highly valid.” The practicality level achieved an average percentage of 94.46%, meeting the criteria for “highly practical.” Meanwhile, the effectiveness level, based on the students’ posttest results, reached 71.43%, meeting the “effective” criterion. Thus, the Canva-assisted interactive flipbook for eighth-grade statistics material is deemed highly valid, highly practical, and effective, making it suitable for use in mathematics instruction to support students’ problem-solving skills.